2004
DOI: 10.1128/jb.186.5.1280-1286.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Symbiosis Island Involved in Horizontal Acquisition of Pederin Biosynthetic Capabilities by the Bacterial Symbiont of Paederus fuscipes Beetles

Abstract: Pederin belongs to a group of antitumor compounds found in terrestrial beetles and marine sponges. It is used by apparently all members of the rove beetle genera Paederus and Paederidus as a chemical defense against predators. However, a recent analysis of the putative pederin biosynthesis (ped) gene cluster strongly suggests that pederin is produced by bacterial symbionts. We have sequenced an extended region of the symbiont genome to gain further insight into the biology of this as-yet-unculturable bacterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
97
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 25 publications
3
97
0
2
Order By: Relevance
“…The presence of similar trans-AT PKS-NRPS gene clusters in different groups of bacteria has suggested that these clusters are horizontally transferred (44). The flanking of the nsp cluster by transposable elements is consistent with this hypothesis, and the mosaic of homologies across the gene cluster suggests involvement of several intergenomic and intragenomic recombination events.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The presence of similar trans-AT PKS-NRPS gene clusters in different groups of bacteria has suggested that these clusters are horizontally transferred (44). The flanking of the nsp cluster by transposable elements is consistent with this hypothesis, and the mosaic of homologies across the gene cluster suggests involvement of several intergenomic and intragenomic recombination events.…”
Section: Discussionmentioning
confidence: 60%
“…2). Furthermore, although the taxonomic identities of their producers are unknown, with the exception of pederin, which is produced by a close relative of Pseudomonas aeruginosa (21,43,44), both lichen metagenomic data and expression and product characterization in Nostoc sp. N6 clearly show that nosperin derives from the cyanobacterial photobiont of P. membranacea.…”
Section: Discussionmentioning
confidence: 99%
“…Further cloning and sequencing of phylogenetically relevant genes outside the PKS system will be necessary to determine whether the symbiont is a member of the genus Pseudomonas as shown for the pederin producer. Because our data indicate that pederin-type genes have been subject to horizontal gene transfer (12), production of the compounds may well be independent from bacterial taxonomy. So far, data about the microbiology of T. swinhoei exist only for a specimen collected at Palau (21).…”
Section: Discussionmentioning
confidence: 88%
“…The fragmentation of the Pseudomonas sp. ped system into three distinct genome regions is most unusual for bacterial PKS pathways but correlates with the large number of transposase pseudogenes that frame the two previously isolated ped regions (9,11,12).…”
Section: Isolation Of a Third Set Of Pederin Genes From Pa Fuscipes mentioning
confidence: 98%
See 1 more Smart Citation